Preservation of Indigenous Women's Traditions and Behavior Within The Framework of Cultural Relativism in Indigenous Communities (A Study of Empirical Approaches in Legal Anthropology) - Handayani, Emy; Suparno, Suparno (Devotion : Journal of Research and Community Service, 2023)
Customs and values within Indigenous communities form the basis of customary behavior in understanding human conduct, particularly in the context of Balinese indigenous women's behavior as guardians of tradition in an empirical approach to legal anthropology. This means that the legal norms used to observe the behaviors of Balinese indigenous women as custodians of indigenous traditions within the frame of cultural relativism represent legal realities apparent in legal situations or any legal events that genuinely occur within the indigenous community, as manifestations of the indigenous women's behaviors in preserving sacred traditions. This is based on an empirical approach to Legal Anthropology. Whether acknowledged or not by the indigenous community, the empirical approach to cultural relativism fundamentally holds a social and cultural value system that can serve as the social capital of the nation. The community's attitudes and behaviors rooted in tradition are guided by values believed to be true, exemplifying the traditional values and cultures passed down through generations and perceived as instruments for social control and religious values that guide human life, manifesting the preservation of local cultural relativism among the local indigenous community. Indigenous communities in these regions become the focal research site with the hope of safeguarding traditional values as a reinforcement of customary practices, the culture, and the traditions of the local indigenous community, which embody the manifestation of protected local wisdom governed by regional customary laws. The methodological approach utilized involves the Empirical Approach of Legal Anthropology linked with the theory of cultural relativism, leading to the conclusion that the approach involves field observations, interviews with research informants, and analyzing primary, secondary, and tertiary data sources through the lens of cultural relativism concerning the behaviors of indigenous women based on an empirical approach within the context of indigenous customary law.